Penerapan Akuntansi Zakat Pada Lembaga Amil Zakat Nasional Inisiatif Zakat Indonesia Cabang Sumatera Utara - Cahyani, Nur; Syafina, Laylan (Universitas Labuhanbatu, 2022)
The purpose of the study is to examine the use of zakat accounting in LAZNAZ Zakat initiative North Sumatra Branch which is an Amil zakat organization. The treasurer of the North Sumatra Zakat initiative is the focus of this study. This is a case study of qualitative descriptive analysis based on primary data collected through a combination of in-depth interviews, documentation, and direct observation, as well as secondary data.The implementation of PSAK 109 on the North Sumatra Zakat initiative is not entirely appropriate, according to the results of the analysis and discussion. Inistiatif ZakatSumatera Utara hanya menyajikanlaporankanperformance (LK) and reportanpengelolaan zakat (LPZ), but the financial report that is made is still in the form of acceptance, as well as the report of the expenditure and distribution report Zakat, Infak/alms (Zis).